Alterações metabólicas resultantes da fosforilação de Isocitrato Liase em Paracoccidioides lutzii - Silva, Karla Christina Sousa (2015)
Paracoccidioidomycosis (PCM) is a systemic mycosis endemic from Latin America caused by the species encompassed in Paracoccidioides genus. This mycosis affects mainly economically active men, who live in rural areas. PCM may cause severe wounds to individuals and is highly incapacitating. This disease is considered a neglected disease by World Health Organization (WHO). When in a hostile environment, like deprivation of carbon sources (6C), fungi tend to use alternative strategies to assist the energetic metabolism. One strategy is using the glyoxylate cycle, which consists in 5 steps, 3 of them being common to the tricarboxylic acid cycle and the other 2 steps are catalyzed by exclusive enzymes from the glyoxylate cycle: isocitrate lyase (ICL) and malate synthase. There are reports in the literature suggesting that phosphorylation of ICL ofis a possible mechanism of enzyme regulation. Phosphorylation is a post-translational ubiquitous ubiquitous and known to modulate the activity / action of many molecules of diverse organisms. In this work, through the use of molecular interactions assays (pull down) using ICL of Paracoccidioides lutzii in its phosphorylated state and non-phosphorylated We found evidence, which suggest that the purine biosynthesis pathway is being used as an alternative way to produce energy to the organism and a high involvement of ICL with amino acids biosynthesis on its non-phosphorylated state. Apparently, phosphorylation works marking ICL to become degraded. This observation may open a new research field through the elaboration of new drugs for PCM treatment using phosphatase inhibitors.